Disease activity trajectories in paediatric lupus and associations with socioeconomic factors and patient-reported pain - E Schmitt; C Smith; V Saper; G Schulert; S Canna; A Grom; E Mellins; S Paul; J Smith; S Wong; A Stephens; S Canny; et al. (Lupus Science and Medicine)
Objective Using data from participants with paediatric SLE (pSLE) in the Childhood Arthritis and Rheumatology Research Alliance Registry, we aimed to: (1) describe 2-year disease activity trajectories, measured by the SLE Disease Activity Index 2000 (SLEDAI 2K); (2) identify characteristics associated with each trajectory and (3) assess achievement of lupus low disease activity state (LLDAS) and associated baseline characteristics.Methods Participants were diagnosed with pSLE within 12 months of baseline visit. Baseline sociodemographic, clinical and treatment characteristics were included in latent trajectory analyses. Associations between patient characteristics with trajectory groups and LLDAS were analysed with multinomial generalised logistic regression modelling.Results 1002 patients were screened; 553 were included for SLEDAI 2K and 269 for LLDAS analyses. SLEDAI 2K trajectories included (T1) low and stable, (T2) high and decreasing, (T3) intermediate and stable. In multinomial generalised logistic regression, baseline SLEDAI 2K score and insurance type were significantly associated with trajectories. 51% (136/269) of patients achieved LLDAS at least once in 24 months as compared with 17% (47/269) at first assessment. LLDAS attainment at both time points was predicted by lower pain interference scores; LLDAS attainment over 24 months was also associated with baseline American College of Rheumatology classification criteria, rituximab use at baseline and highest completed level of parent/guardian education.Conclusions Disease activity trajectories in a pSLE cohort were predicted by baseline SLEDAI 2K and insurance. Only half of the patients achieved LLDAS during the 2-year study period, which was predicted by baseline characteristics including pain interference. The relationship between disease activity and socioeconomic factors and pain warrants further investigation to identify modifiable factors to reduce pSLE disease activity.